Bride [large type] - Hazelwood, Ali (Thorndike Press large print romance series., 2024)
"Misery Lark, the only daughter of the most powerful Vampyre councilman of the Southwest, is an outcast--again. Her days of living in anonymity among the Humans are over: she has been called upon to uphold a historic peacekeeping alliance between the Vampyres and their mortal enemies, the Weres, and she sees little choice but to surrender herself in the exchange--again... Weres are ruthless and unpredictable, and their Alpha, Lowe Moreland, is no exception. He rules his pack with absolute authority, but not without justice. And, unlike the Vampyre Council, not without feeling. It's clear from the way he tracks Misery's every movement that he doesn't trust her. If only he knew how right he was.... Because Misery has her own reasons to agree to this marriage of convenience, reasons that have nothing to do with politics or alliances, and everything to do with the only thing she's ever cared about. And she is willing to do whatever it takes to get back what's hers, even if it means a life alone in Were territory...alone with the wolf"--